Beam-contamination-induced compositional alteration and its neutron-atypical consequences in ion simulation of neutron-induced void swelling. Issue 7 (3rd November 2017) - Gigax, Jonathan G.; Kim, Hyosim; Aydogan, Eda; Garner, Frank A.; Maloy, Stu; Shao, Lin
ABSTRACT: Although accelerator-based ion irradiation has been widely accepted to simulate neutron damage, neutron-atypical features need to be carefully investigated. In this study, we have shown that Coulomb force drag by ion beams can introduce significant amounts of carbon, nitrogen, and oxygen into target materials even under ultra-high vacuum conditions. The resulting compositional and microstructural changes dramatically suppress void swelling. By applying a beam-filtering technique, introduction of vacuum contaminants is greatly minimized and the true swelling resistance of the alloys is revealed and matches neutron behavior closely. These findings are a significant step toward developing standardized procedures for emulating neutron damage. GRAPHICAL ABSTRACT: IMPACT STATEMENT An innovative 'beam shaking' technique is proposed to reduce beam-induced impurity contamination in accelerator-based ion irradiation. Without this technique, void swelling of ion-irradiated alloys can be greatly underestimated.